Peningkatan Kemampuan Berhitung Melalui Media Kartu Angka Pada Anak Didik Kelompok B Semester I TK Pertiwi I Kedungrejo Kecamatan Tunjungan Kabupaten Blora Tahun 2015/2016 - Sukartini, Siti, Dr. Surtikanti, SH, MH (2015)
Conducted research on the initials TK Pertiwi I Kedungrejo District of Tunjungan. Subjects Research hearts husband is Learners Group B TK Pertiwi I KedungrejoBlora. Improved implementation is carried out through USE husband Learning Media Card Numbers The given at learners all students group B TK Pertiwi I Kedungrejo through prayer cycle learning. The research method used is a Class Action Research (PTK) which consists up 2 cycle. Subjects were students learners TK Pertiwi I Kedungrejo as many as 20 children. Data analysis using descriptive analysis techniques to compare the comparative with initial conditions the results achieved in each cycle, and a qualitative descriptive analysis results comparing the findings with observation observation and reflection on pre-cycle, cycle I, dan cycle II. Based on the findings of research that has been done and data research analyst the findings lead on each cycle learning, obtained conclusion that, through use figures media card counting ability to increase the ability for children in kindergarten TK Pertiwi I Kedungrejo academic year 2015/2016. From the findings Numeracy before upgrading measures showed results on average 49.65% of taxable income be taken in the first cycle increased by 20.65% to 70.30%. End on cycle II increased by 11.41% to 81.71%. Such increase has reached indicator of success, ie obtaining developing criteria according to hope.